2003
DOI: 10.5858/2003-127-178-iirrin
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune-Related Receptors in Normal and Psoriatic Skin

Abstract: Context.—A precise role for the innate immune system in psoriasis remains to be determined. Surface receptors, including Toll-like receptors (TLRs) that recognize bacterial ligands and CD91, which recognizes heat shock proteins (HSPs), are implicated in both innate and adaptive immunity. Objective.—Since skin is exposed to various exogenous stimuli, which can provoke or exacerbate psoriasis, we characterized expression and function of TLRs, CD91, and HSPs in normal and psoriatic skin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(17 citation statements)
references
References 46 publications
0
11
1
5
Order By: Relevance
“…32,33 In recent years, the observation that psoriatic plaques are resistant to microbial infection despite a compromised skin barrier has led to growing interest in functions of the innate immune system in psoriatic skin. [34][35][36] A role for innate immune responses as a trigger of the pathogenic T-cell cascade leading to psoriasis has been suggested; however, there is no direct evidence. Murine models have demonstrated that TLR activation may provide signals to elicit T-cellmediated autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 In recent years, the observation that psoriatic plaques are resistant to microbial infection despite a compromised skin barrier has led to growing interest in functions of the innate immune system in psoriatic skin. [34][35][36] A role for innate immune responses as a trigger of the pathogenic T-cell cascade leading to psoriasis has been suggested; however, there is no direct evidence. Murine models have demonstrated that TLR activation may provide signals to elicit T-cellmediated autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical relevance of this finding is illustrated by the observation that expression of these receptors is significantly increased in psoriasis lesional skin. Although the expression of family members of the TLR family was studied extensively in human KCs and psoriatic skin (Song et al, 2002;Baker et al, 2003;Curry et al, 2003;Mempel et al, 2003;Pivarcsi et al, 2003;Kollisch et al, 2005;Lebre et al, 2007), minimal data are available on the expression of the RNA helicases RIG-I and MDA5 in KCs and inflamed skin.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes (KCs), the major cell type present in the epidermis, can exert many immunological functions such as cytokine and chemokine production, cell adhesion, and antigen presentation, and can therefore be regarded as immunecompetent cells. KCs are responsive to stimulation with various PAMPs, and TLR expression on human KCs has been studied extensively (Song et al, 2002;Baker et al, 2003;Curry et al, 2003;Mempel et al, 2003;Pivarcsi et al, 2003;Kollisch et al, 2005;Tohyama et al, 2005;Lebre et al, 2007). In contrast, very little is known about KCs expression of members of the other families of pattern recognition receptor families such as the NOD-like receptors or the RIGlike helicases.…”
Section: Introductionmentioning
confidence: 99%
“…13 El complejo CD14-TLR4/4MD-2 se une al lipopolisacárido (LPS) de bacterias Gram-negativas, a la proteína F viral (induce la secreción de proteínas de choque térmico), 14,15 el TLR5 se une a la flagelina bacteriana, 16,17 y el TLR9 que se encuentra en el retículo endoplásmico participa en la iniciación de la respuesta inmune, seguida al daño epidérmico o infección. [18][19][20] El objetivo de este trabajo es demostrar la presencia in situ de los receptores TLR2 y TLR4, en queratinocitos de piel, en cortes de pacientes con actinomicetoma por Actinomadura madurae, mediante el uso de técnicas inmunohistoquímicas.…”
Section: Antecedentesunclassified